Summer Grazing of Steers in Western Kansas - Dhuyvetter, Kevin C.; Tonsor, Glynn T. (My University, 2012)
This publication is a guide to budget estimate costs and returns for a season-long and an early-intensive grazing system in Western, KS.
MF1007_2012-12
Keywords: MF1007; Economics; Livestock; MF